Comparison of Modeling Volatility of Indonesia Banks Using ARCH, GARCH, TARCH and EGARCH - Eneng Nur Hasanah (Universitas Islam Bandung, 2018)
ABSTRACT According to the rating of PEFINDO, there are 10 biggest Banks in Indonesia which dominate 65.2% of the total asset. From this rating, writer examine the best fitted volatility model using ARCH, GARCH, TARCH and EGARH. The result from R-Squared, AIC and SIC, all of the bank have good fitted volatility with EGARCH model, but when writer double checking for the EGACRH model with time series diagnostic checking and fitted model performance measurement, the result show that not all of the banks is fitted volatility by EGARCH model. ABSTRAK Menurut peringkat PEFINDO, ada 10 Bank terbesar di Indonesia yang mendominasi 65,2% dari total aset. Dari peringkat ini, penulis menguji model volatilitas yang paling cocok menggunakan ARCH, GARCH, TARCH dan EGARH. Hasil dari R-Squared, AIC dan SIC, semua Bank memiliki volatilitas yang sesuai dengan model EGARCH, tetapi ketika penulis memeriksa dua kali untuk model EGACRH dengan pemeriksaan diagnostik deret waktu dan pengukuran fitted model performance, hasilnya menunjukkan bahwa tidak semua Bank masuk ke dalam kategori volatilitas dengan model EGARCH